PENGARUH METODE PERMAINAN JUNGLE MATH SURVIVE TERHADAP HASIL BELAJAR BANGUN RUANG SISWA KELAS V SD SWASTA AL-WASHLIYAH SEI RAMPAH - Fanny Rahmasari; Samsul Bahri (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to determine the effect of the jungle math survival method on learning outcomes, before being given treatment, the validity test was carried out on both learning outcome variables (pretest and posttest) showing that all question items on the measuring instrument can be used validly in collecting research data with the results of the rcount> rtable value for both variables. Furthermore, the reliability test of the question instrument on pretest and posttest data has a fairly high level of reliability. This is indicated by the Cronbach Alpha value which is close to 1, namely 0.791 for pretest data and 0.806 for posttest data. The pretest and posttest data in this study meet the normality requirements or follow a normal distribution. This is confirmed by the results of the normality test (Kolmogorov-Smirnov) which shows a significance value greater than the specified significance level. There is a significant difference between the pretest and posttest means. The Independent Samples Test showed that the mean of the posttest group was lower than the pretest group, with a difference of -11.875. The variance between the pretest and posttest groups on the learning outcomes variable is homogeneous. The results of the homogeneity of variance test (Test of Homogeneity of Variance) show that the significance value is greater than the specified significance level. Paired Samples Test analysis showed that there was a significant difference between the pretest and posttest, with an average decrease in scores of -12.500. The 95% confidence range for the difference is -14.318 to -10.682. Based on the explanation above, it can be concluded that the Jungle Math Survive method has a significant impact on changes in learning outcomes.